The Correlation between Students’ Habit on Watching English Movie and Their Listening Skill at the Tenth Grade of SMK Prima Bakti Citra Raya Kabupaten Tangerang in Academic Year 2019/2020 - Pranata, Ardi (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
ABSTRACT The goal of this study is to determine the relationship between students' habit of watching English movies (X) and their listening competence (Y) in the tenth grade at SMK Prima Bakti Kab. Tangerang in the academic year 2019/2020. This study's sample size was obtained by employing a random sampling procedure on 30 students. The data was analyzed using Pearson Product Moment Correlation, with the instruments being students' listening scores and a questionnaire on their habit of watching English films. As a result, the findings of the study revealed that there is a very weak link between students' habit of watching English movies and their listening ability. In conclusion, in the academic year 2019/2020, there is a very low link between students' habit of watching English movies and their listening skills at SMK Prima Bakti Kab. Tangerang. However, additional investigation revealed that this conclusion was influenced by a number of internal dangers. The purpose of this study is to see if there is a link between students' habit of watching English movies (X) and their listening ability (Y) in the tenth grade at SMK Prima Bakti Kab. Tangerang in the 2019/2020 academic year. The sample size for this study was determined by using a random sampling approach on 30 students. The data was evaluated using the Pearson Product Moment Correlation. Keyword: Listening skill, Watching English movie